PENGOLAHAN MOTIF YANG TERINSPIRASI DARI TENUN GRINGSING WAYANG KEBO DENGAN TEKNIK DIGITAL PRINTING PADA PRODUK WOMENSWEAR - Made Devi Savitri Wirawan; Morinta Rosandini (Serat Rupa: Journal of Design, 2021)
Seeing the visual potential from motif visual of Tenun Gringsing Wayang Kebo which is a sacred textile that manually weaved by the people of Desa Tenganan Pagringsingan and known as a double weaved cloth with full of philosophy meaning and seeing the potential to make an innovation of the new pattern composition using ornament that in Tenun Gringsing Wayang Kebo motif to create the new motif innovation which is inspired by Tenun Gringsing Wayang Kebo. Using qualitative method applied for thisresearch by doing the study literature of philosophy and ornament analysis from the Wayang Kebo pattern and a re-arrange the pattern ornament experiment with doing a stilation motif shape and composition that inspired by Tenun Gringsing Wayang KeboThe result of the experiment applied using surface design technique which is digital printing and beading embellishment with polyester and organza material that can applied into a fashion product. The result of shape stilation and motif composition experiment with symmetrical motif pattern and half-drop repetition technique, applied into the soft color as a innovation and modern form. The result of this research is the collection with a modern style and later, will be applied into a womenswear ready-to-wear design. The purpose from creating new motif is to lift the local culture to become a developed new motif potential also become a modern ethnic fashion design reference for designers, business people and society